Analysis of the impact of harmonic interference circuit Costas - B. I. Shakhtarin; Yu. A. Sidorkina; T. G. Aslanov (Научный вестник МГТУ ГА, 2016)
The analysis of influence of harmonic interference on the phase error in the Costas circuit is carried out. Differential equations of the circuit are obtained. Are obtained in the zero and first approximation the equations of the phase error for the Costas circuit. The simulation in MatLab environment of phase error introduced by the Costas circuit in the first approximation and the graphs of this error is carried out. On the basis of mathematical model, by the phase error counts were obtained graphs of probability density functions of the signal errors introduced by the model. A simulation model of the Costas circuit in the Simulink environment is given. In the simulation model, by the phase error counts in MatLab, were obtained graphs of probability density functions of the signal error due to the simulation model. The comparison of the obtained results of the Costas circuit analysis obtained by mathematical modeling of the phase error equation in the first approximation with simulation results in Simulink environment shows that the results of mathematical modeling rather accurately coincide with the simulation results. On the basis of simulation were obtained the graphs of the average time before mistracking for various values of the interference to signal ratio